Global Financial Development Report 2019/2020 : Bank Regulation and Supervision a Decade after the Global Financial Crisis - World Bank (Washington, DC: World Bank, 2019)
Over a decade has passed since the collapse of the U.S. investment bank Lehman Brothers marked the onset of the largest global economic crisis since the Great Depression. The crisis revealed major shortcomings in market discipline, regulation, and supervision, and reopened important policy debates on financial regulation. Since the onset of the crisis, emphasis has been placed on better regulation of banking systems and on enhancing the tools available to supervisory agencies to oversee banks and intervene speedily in case of distress. Drawing on 10 years of data and analysis, the Global Financial Development Report 2019/2020 uncovers new evidence on the regulatory remedies adopted to prevent future financial troubles, and particularly the impact of reforms on market discipline and bank capital. Countries should design and enforce regulations that are appropriate for the institutional environment, strength of market discipline, supervisory capacity, and business models of banks in a given country. Regulations also need to be compatible with incentives, but designing and enforcing such regulations are complex tasks, particularly where sophisticated markets do not exist and institutions are underdeveloped. Globalization and technological change are important trends that make it even more challenging to provide effective oversight of banks. The Global Financial Development Report 2019/2020 is the fifth in a World Bank series. The report also tracks financial systems in more than 200 economies before and during the global financial crisis on an accompanying website (http://www.worldbank.org/en/publication/gfdr) and provides information on how banking systems are regulated and supervised around the world (http://www.worldbank.org/en/research/brief/BRSS).